Transendensi Kasi Makan Laut dalam Ritual Adat di Kepulauan Banda - Latora, Rusdan (BANDA HISTORIA: Jurnal Pendidikan Sejarah dan Studi Budaya, 2024)
In the context of the cultural ritual traditions of the Banda people, this abstract aims to investigate the transcendent meaning of feeding the sea. This research was conducted in Banda District, Regency, Central Maluku. A philosophical approach is the basis of the research methodology used in this paper. The research results show that the traditional ritual of feeding the sea in Banda is still carried out and has transcendental, religious, ethical, and mystical meaning. This shows the harmonious relationship between humans and the Creator, fellow humans, and the universe. Understanding symbols such as sacredness, togetherness, and the balance of nature (the sea) is used as part of the politics of community hope to ensure that the village community desires to avoid disasters and dangers, as well as the potential benefits of the sea for the lives of the Banda community. This study shows that the ritual of feeding the sea creates social, cultural, and economic identity and strengthens the spiritual connection and highest religious values of the Bandan community. Taking a deep understanding of the transcendental in the ritual of feeding the sea means following transcendence and becoming one's identity as a Bandanese people.